2016
DOI: 10.1080/03235408.2016.1181945
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among four triazole fungicides on growth and development of sheath blight of rice pathogenRhizoctonia solaniKühn AG1-1A

Abstract: The sheath blight of rice pathogen Rhizoctonia solani Kühn AG1-1A has long been known as a major crisis in global rice production. The present study aimed to compare the efficacy of four triazole fungicides at different doses on the growth and development of R. solani Kühn AG1-1A. Obtained results demonstrated inhibitory effects of all four fungicides on mycelial growth, sclerotia formation and biomass production of R. solani Kühn AG1-1A with significant variation among the treatment doses as well as fungicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Difenoconazole and tebuconazole were effective against both strains of R. solani tested in vitro trials. This is in accord with other studies that showed the e cacy of these two fungicides against R. solani (Shan-lin 2013; Datta et al 2016). In addition, our results show that the cultivation of sugar beet seeds in PDA medium containing difenoconazole caused no damage to seedlings.…”
Section: Discussionsupporting
confidence: 92%
“…Difenoconazole and tebuconazole were effective against both strains of R. solani tested in vitro trials. This is in accord with other studies that showed the e cacy of these two fungicides against R. solani (Shan-lin 2013; Datta et al 2016). In addition, our results show that the cultivation of sugar beet seeds in PDA medium containing difenoconazole caused no damage to seedlings.…”
Section: Discussionsupporting
confidence: 92%
“…Management of these fungal soilborne pathogens is challenging since the fungal propagules exist in the soil, causing difficulties in controlling them. Synthetic fungicide applications such as triazole, carbendazim, carboxin, and thiram have been used to suppress the growth of R. solani (Akhter et al 2015;Datta et al 2016). However, continuous application of fungicides, particularly in an endemic area is considered unfriendly environmental control, that may affect other living organisms such as beneficial soil microbes, and also leading to strain resistance to certain active compounds of the fungicides (Sundaramoorthy and Balabaskar 2013).…”
Section: Introductionmentioning
confidence: 99%
“…12 Therefore, effective control of sheath blight in rice is mainly achieved by the application of chemical fungicides. 13 Nonhost resistance can be another alternative to host resistance and chemical control against R. solani. Nonhost disease resistance is considered more durable against most studied pathogens and it works against all isolates of a specific pathogen.…”
mentioning
confidence: 99%